KESİRLİ DİFERİNTEGRAL YARDIMIYLA GENELLEŞTİRİLMİŞ LAGUERRE DİFERENSİYEL DENKLEMLERİN ÇÖZÜMLERİ - KARABULUT, SERKAN (Fırat Üniveristesi, 2018)
Matematiksel analizin bir kolu olan kesirli analiz, türev ve integralin tam sayı olmayan mertebelere genişletilmiş halidir. Fen ve mühendislikte oldukça geniş uygulama alanına sahiptir. Amacımız; ikinci mertebeden lineer diferensiyel denklemler için kesirli analiz yardımıyla özel çözümler elde etmektir. Bu tezde ilk olarak; kesirli analizin tanım, teorem ve özeliklerinden bahsedilmiştir. Sonra Fizik ve mühendislik alanlarında karşılaşılan zamanda bağımsız Schrödinger denklemi ele alınmıştır. Bu tür denklemler doğrusal ikinci mertebeden kısmi diferensiyel denklemlerdir. Analitik çözümlerini elde etmek için, değişkenlerin ayrılması, Green fonksiyonları ve integral dönüşümler en çok kullanılan yöntemlerdir. Bu çalışmada küresel koordinatlarda değişkenlerin ayrılması yöntemi kullanılarak açısal ve radyal kısmın sağladığı denklemler elde edilmiştir. Radyal kısmın sağladığı denklemde, uygun dönüşümler yapılarak Laguerre diferensiyel denklemi elde edilmiştir. Daha sonra singüler noktalara sahip, homojen ve homojen olmayan Laguerre diferensiyel denkleminin kesirli analiz yardımıyla özel çözümleri elde edilmiştir. Anahtar Kelimeler: Kesirli diferintegral, Kesirli analizi, Laguerre denklemi

Fractional calculus, a branch of mathematical analysis, is the generalization of derivative and integral to the non-integer order. It has quite wide application area in science and engineering. Our aim is to obtain particular solutions for the second order linear differential equations with the help of fractional analysis. In this thesis; firstly, definition, theorems and properties of fractional analysis are mentioned. Then, the Schrödinger equation, witch is the time-independent in the fields of physics and engineering, is considered. These type equations are linear and secondorder partial differential equations. Separation of variables, Green's functions, and integral transforms are among the most frequently used techniques for obtaining their analytic solutions. In this study, the equations provided by angular and radial part are obtained by using the method of separating variables in the spherical coordinates. In the equation provided by the radial part, Laquerre differential equation was obtained by making appropriate transformations. Later particular solutions of homogeneous and non-homogeneous Laquerre differential equation with singular points are obtained with the help of fractional analysis. Keywords: Fractional differintegral, Fractional analysis, Laquerre equation
Solutions of the generalized Laguerre differential equation with the help of fractional differintegral
Keywords: Matematik